The Relationship between Organizational Virtuousness and Job Performance: The Moderating Role of Psychological Well-Being«An Empirical Study on the Hospitals and Medical Centers at Mansoura University in Egypt» - Elmansi, Mahmoud (The Arab Journal of Administration, 2022)
The purpose of this study is to investigate how organizational virtuousness (OV) and psychological well-Being (PW) explain job performance (JP). This study also aims to examine the influence of psychological well-Being, as a moderator, on the relationship between organizational virtuousness and Job Performance. Primary data was collected based on a questionnaire collected from a sample consisting of 362 nursing staff working in hospitals and medical centers at Mansoura university in Egypt, among them was 314 valid surveys with a response rate of 86.7%. Partial least Square (PLS) was used to validate and test the measurement and structural models. The finding revealed that organizational virtuousness, as a multidimensional constructs, and psychological well-Being were significant determinants of Job performance. Besides the significant direct effect, psychological well-Being was found to be a significant moderator and was able to strengthen the relationship between organizational virtuousness and job performance.